Foreign Trade of Nepal: An Outline of India and Overseas Economies - Upadhyaya, Yadav Mani; Kharel, Khom Raj; Poudel, Omkar (Saptagandaki Journal, 2021)
Background: This article seeks to explain the current status of Nepal's involvement in foreign trade. The major objective of this research is to look into Nepal's present foreign trade situation with India and the rest of the world Methods: The study used a 29-years of time series data related to foreign trade, breaking down global foreign trade, Indian foreign trade, and overseas foreign trade one by one. Graphs, a simple regression model, and a log linear model are used for analysing the data. Results: This study found a positive relationship between economic growth and both imports and exports. However, an export equal to one million can generate only 0.00133 million income for Nepal. Also, imports generate only 0.03451 million revenue of Nepal which is very low. Conclusion: Foreign trade is essential for Nepal's economic growth, yet it is still a long way off.